2022
DOI: 10.3390/ijms23084357
|View full text |Cite
|
Sign up to set email alerts
|

PcWRKY11, an II-d WRKY Transcription Factor from Polygonum cuspidatum, Enhances Salt Tolerance in Transgenic Arabidopsis thaliana

Abstract: Being an invasive plant, Polygonum cuspidatum is highly resilient and can survive in unfavorable environments for long periods; however, its molecular mechanisms associated with such environmental resistance are largely unknown. In this study, a WRKY transcription factor (TF) gene, PcWRKY11, was identified from P. cuspidatum by analyzing methyl jasmonate (MeJA)-treated transcriptome data. It showed a high degree of homology with WRKY11 from Arabidopsis thaliana, containing a WRKY domain and a zinc finger struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…GbMYB5 also confers drought tolerance to cotton and genetically modified tobacco plants [ 20 ]. PcWRKY11, from Polygonum cuspidatum , enhances salt tolerance in transgenic Arabidopsis thaliana [ 21 ]. Overexpression of the apple MdMYB121 gene significantly enhanced the tolerance of transgenic tomato and apple plants to high salt and drought stress [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…GbMYB5 also confers drought tolerance to cotton and genetically modified tobacco plants [ 20 ]. PcWRKY11, from Polygonum cuspidatum , enhances salt tolerance in transgenic Arabidopsis thaliana [ 21 ]. Overexpression of the apple MdMYB121 gene significantly enhanced the tolerance of transgenic tomato and apple plants to high salt and drought stress [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Soluble proteins are proteins that can be dissolved in water or other solvents as small molecules. A variety of plant studies ( Chen L. et al, 2020 ; Wang et al, 2022 ) have shown that under adverse conditions, accumulated soluble substances can regulate cell fluid concentration to regulate osmotic pressure, indicating stress resistance. In this study, we aimed to determine the state of T. hemsleyanum under UV stress by measuring these three indicators.…”
Section: Resultsmentioning
confidence: 99%
“…The transcription level of CsWRKY25 (Group I) is up-regulated in Penicillium digitatum -infected citrus peels ( Wang et al, 2022b ). PcWRKY11 (Group II WRKY from Polygonum cuspidatum ) significantly increases the tolerance to salt stress in transgenic A. thaliana ( Wang et al, 2022a ).…”
Section: Discussionmentioning
confidence: 99%